Literacy in context : Language of pre-1914 literature - Buckley, Pauline; Flower,Celeste (University of Cambridge : New York, 2002)
Literacy in Context is your key to delivering the Framework for Teaching English. Each book will help students to understand more about a particular kind of writing, learn about its language features and work towards their own piece of writing in a similar style.
Keywords: Language; Literature